2017
DOI: 10.1002/etc.3992
|View full text |Cite
|
Sign up to set email alerts
|

A review of measured bioaccumulation data on terrestrial plants for organic chemicals: Metrics, variability, and the need for standardized measurement protocols

Abstract: Quantifying the transfer of organic chemicals from the environment into terrestrial plants is essential for assessing human and ecological risks, using plants as environmental contamination biomonitors, and predicting phytoremediation effectiveness. Experimental data describing chemical uptake by plants are often expressed as ratios of chemical concentrations in the plant compartments of interest (e.g., leaves, shoots, roots, xylem sap) to those in the exposure medium (e.g., soil, soil porewater, hydroponic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 78 publications
2
55
0
Order By: Relevance
“…As noticed, when log RCF (soil) is plotted against log K ow in Fig. 2(A), no distinct patterns emerge (R 2 < 0.16), as recognized in various reports (Cai et al, 2008; Doucette et al, 2018; Macherius et al, 2012; Mikes et al, 2009; Scheunert et al, 1994; Takaki et al, 2014; Tao et al, 2009; Trapp et al, 1990; Wu et al, 2012). Here the RCF (soil) at a given K ow varies by as high as 1400 -fold.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…As noticed, when log RCF (soil) is plotted against log K ow in Fig. 2(A), no distinct patterns emerge (R 2 < 0.16), as recognized in various reports (Cai et al, 2008; Doucette et al, 2018; Macherius et al, 2012; Mikes et al, 2009; Scheunert et al, 1994; Takaki et al, 2014; Tao et al, 2009; Trapp et al, 1990; Wu et al, 2012). Here the RCF (soil) at a given K ow varies by as high as 1400 -fold.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, many observed RCF (soil) values are < 1, which is in contrast with the trend for organic chemicals concentrating from water into an organic phase. In analyzing a large set of chemical soil-plant data, Doucette et al (2018) and Takaki et al (2014) found a similar wide scatter in plots of log RCF (soil) versus log K ow . The lack of a specific relation between log RCF (soil) and log K ow comes with no surprise in view of C s = f om C om for relatively water-insoluble (high- K ow ) chemicals with a water-saturated soil, where the soil contamination intensity C om is independent of the value of f om (see more discussion in Hung et al, 2009).…”
Section: Resultsmentioning
confidence: 77%
“…Crops contain enzymatic systems such as cytochrome P-450s and their (bio)transformation capacity may be compound as well as crop specific. Non-ionizable, polar, highly water-soluble organic compounds are most likely to be taken up by crops and translocated to shoot tissue (Doucette et al 2018).…”
Section: Intrinsic Properties Of Organic Coecsmentioning
confidence: 99%
“…Soil is defined as the part of the solid earth that has been altered by the loosening of the earth, humus formation, and chemical decomposition, and by the transportation of humidification and chemical decomposition products [7,[10][11][12][13][14][15][16][17][18][19]. However, when it is examined in detail, soil is a complex structure and the biological and biochemical processes in it are the basis of the terrestrial ecosystems [7,8,[10][11][12][13][14][15][16][17][18][19]. In this respect, it is imperative to examine health changes of the soil and to determine its relationship with the plant.…”
Section: Introductionmentioning
confidence: 99%